Socio-demographic factors and diet-related characteristics of community-dwelling elderly individuals with dysphagia risk in South Korea - Lim, Youngsuk; Kim, Chorong; Park, Haeryun; Kwon, Sooyoun; Kim, Oksun; Kim, Heeyoung; Lee, Youngmi (Nutrition research and practice, 2018)
The objective of this study was to determine dysphagia risk among community-dwelling elderly people living at home. We also examined the impact of socio-demographic variables on dysphagia risk as well as the relationship between dysphagia risk and dietary characteristics. The study sample included 568 community-dwelling individuals, aged 65 years and above, who were living independently in their own home in Seoul, Gyeonggi, or Gwangju in South Korea. We used a dysphagia risk assessment scale to screen for dysphagia risk and the Mini nutritional assessment to evaluate the nutritional status. Associations between dysphagia risk and other variables were assessed using logistic regression analysis. Of the 568 subjects, 350 (61.6%) were classified into the dysphagia risk group (DR) and 218 (38.4%) were classified into the normal group (non-DR). Being female (odds ratio (OR) = 1.82, 95% confidence interval (CI) = 1.28-2.59), being 75 years and older (OR = 2.40, 95% CI = 1.69-3.42), having a lower education level (OR = 2.29, 95% CI = 1.33-3.97), and having a lower perceived economic status (OR = 2.18, 95% CI = 1.32-3.60) were more frequently observed with dysphagia risk compared to those who did not have such characteristics. Lowered mastication ability (OR = 14.40, 95% CI = 4.43-46.95), being at risk of malnutrition or malnourished (OR = 2.72, 95% CI = 1.75-4.23), lowered appetite (OR = 3.27, 95% CI = 2.16-4.93), and decreased food intake (OR = 2.95, 95% CI = 1.83-4.78) were observed more frequently in the DR group than in the non-DR group when adjusting for potential confounding factors. It is necessary to develop and apply integrated programs to improve the dietary habits and nutritional status of elderly individuals at risk for dysphagia, especially for women aged 75 years or older with lower educational and economic levels.